2022
DOI: 10.3897/jucs.94133
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection and Recognition of Citrus Fruit & Leaves Diseases for Precision Agriculture

Abstract: Machine learning is a branch of computer science concerned with developing algorithms & models capable of ‘learning through data and iterations’. Deep learning simulates the structure and function of human organs and diseases using artificial neural networks with more than one hidden layer. The primary purpose of this work is to develop and test computer vision and machine learning algorithms for classifying Huanglongbing (HLB)-infected, healthy, and unhealthy leaves and fruits of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Additionally, a survey by Saini et al [1] regarding various approaches for detecting and classifying diseases in citrus plant leaves revealed that image preprocessing strategies contribute to increasing segmentation precision. During this survey, the k-means technique was the most critical segmentation strategy for diseased plants.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a survey by Saini et al [1] regarding various approaches for detecting and classifying diseases in citrus plant leaves revealed that image preprocessing strategies contribute to increasing segmentation precision. During this survey, the k-means technique was the most critical segmentation strategy for diseased plants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Any nation's economic development depends heavily on agricultural productivity. Saini et al [1] stated that disease identification in plants is vital in the agricultural sector, as plant disease is common. Thus, the development of tools to early detect pests and diseases would be a great tool to prevent their continuous widespread.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, weed and crop detection have attracted many researchers to propose and develop methods using different machine learning and Deep Learning (DL) techniques, for example, automated classification of crop and weed [23,20,30,18,3], segmentation of weed-crop [31]. In [22], Convolutional Neural Networks (CNNs) was proposed to classify the plants into dock, clover and grass and to solve formidable challenges due to the images complexity.…”
Section: Related Workmentioning
confidence: 99%
“…Every sector of the economy relies on this function. sincerely want to increase fruit output on farmland, then must make sure that fruit farming is sustainable in terms of disease control [3,4]. The amount of minerals and nutrients inside fruits has a considerable impact on the cultivation methods employed for apples, oranges, grapefruits, pomegranates, and plums.…”
Section: Introductionmentioning
confidence: 99%